Antibacterial Activity Test of Sumbawa White Honey against Escherichia coli ATCC 25922 - Hulfifa, Lale Nandita; Rosyunita, Rosyunita; Wardoyo, Eustachius Hagni; Hasbi, Nurmi; Rahim, Adelia Riezka; Arnawati, Ida Ayu; Alamsyah, Abiel Dwi Cahya Firdaus; Vaidika, I Komang Satya; Hazaa, Saskia Safarina (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Due to their high mortality and morbidity rates, E. coli infections are a serious issue. Antimicrobial Resistance (AMR) is a result of this indiscriminate antibiotic use. One approach to address this issue is to utilize natural antimicrobials such as Sumbawa white honey. Sumbawa white honey contains antibacterial components like glucose and fructose (80%), water (17%), polyphenols, and hydrogen peroxide. This study aimed to analyze the antibacterial activity of white honey from Sumbawa against E. coli ATCC 25922. The research method employed was a laboratory experiment using a post test only control group design. Antibacterial testing was conducted using disc diffusion at concentrations of 25%, 75%, and 100%, with chloramphenicol as positive control and DMSO as negative control, and honey processing involved dilution. Antibacterial tests were repeated five times and antibacterial activity was observed based on the diameter of inhibition zones around the disc. The outcomes showed that there was a restraint zone at 100 percent grouping of honey, to be specific 0.90 mm, while at 25% and 75% fixations there were no hindrance zones. According to the findings of this study, white honey from Sumbawa has a low antibacterial activity (0.90 mm), but this activity is ineffective against E. coli ATCC 25922. Further identification of the chemical components in Sumbawa white honey that are primarily responsible its antibacterial effect.